2017
DOI: 10.1007/s00191-017-0491-y
|View full text |Cite
|
Sign up to set email alerts
|

Development blocks in innovation networks

Abstract: The notion of development blocks (Dahmén, 1950, 1991) suggests the co-evolution of technologies and industries through complementarities and the overcoming of imbalances. This study proposes and applies a methodology to analyse development blocks empirically. To assess the extent and character of innovational interdependencies between industries the study combines analysis of innovation biographies and statistical network analysis. This is made possible by using data from a newly constructed innovation output … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 84 publications
0
5
0
Order By: Relevance
“…Despite the prominent role of innovation in surgery, only limited attention has been paid to quantifying its value as a function of diffusion processes and implementation. An effective way to model the global spread of ideas, knowledge, and innovation is through network analysis [ 21 , 22 ]. Network analysis has been previously used in surgical research but only in the context of network meta-analysis and scientific collaboration networks [ 23 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the prominent role of innovation in surgery, only limited attention has been paid to quantifying its value as a function of diffusion processes and implementation. An effective way to model the global spread of ideas, knowledge, and innovation is through network analysis [ 21 , 22 ]. Network analysis has been previously used in surgical research but only in the context of network meta-analysis and scientific collaboration networks [ 23 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Historical studies have shown that while some radical innovations only influence a specific sector, others may affect a whole range of sectors or, in rare cases, the entire economy (Perez, 2002(Perez, , 2009b. Radical innovations or clusters of innovations can thus set in motion "a series of everwidening concentric circle" of change (Rosenberg, 1982) that create a "sequence of widening imbalances" in the economy (Dahmén, 1989;Taalbi, 2016).…”
Section: Innovation and Multi-sectoral Dynamicsmentioning
confidence: 99%
“…The GFC is associated with permanent declines in industrial production, investment and productivity, and this applies to both companies (Ahn, Duval & Sever, 2018), industries (Dell'Ariccia, Detragiache & Rajan 2008Kroszner, Leaven & Klingebiel, 2007) and the macroeconomic scale (Cerra & Saxena, 2017;Kołodko, 2020). As it was, the GFC caused a reduction of the external R&D financing channel, patent and innovation financing by blocking long-term corporate investments, hindering the return of economic activity to the original path of growth (Cerra & Saxena, 2008, 2017Furceri & Zdzienicka, 2011;Reinhart & Rogoff, 2009;Teulings & Zubanov, 2014). In the process of restricting the external financing of innovations in the crisis, an actual reallocation of bank loans from innovative to non-innovative companies was observed because of excessive risk coming with innovative activity (Hall & Lerner 2010;OECD, 2012;Benoliel & Gishboliner, 2015;Markatou & Vetsikas, 2015;Nanda & Nicholas, 2014;Aghion, Askenazy, Berman, Cette, & Eymard, 2012;de Ridder, 2019;Peia, 2019).…”
Section: The Reality Of the Crisis In The Light Of The Covid-19 Pande...mentioning
confidence: 99%